Apolipoprotein AV variants do not affect C-reactive protein levels in Caucasian males - Hubácek, J A; Skodová, Z; Lánská, V; Stávek, P; Adámková, V; Poledne, R (Physiological research, 2005)
The important role of APOAV gene variants in determination of plasma triglyceride levels has been shown in many population studies. Recently, an influence of APOAV T-1131>C polymorphism on C-reactive protein (CRP) in young Korean males has been reported. We have therefore analyzed a putative association between T-1131>C, Ser19>Trp and Val153>Met APOAV variants (PCR and restriction analysis) and CRP concentrations in 1119 Caucasian males, aged between 28 and 67 years (49.2+/-10.8 years). The frequency of C allele carriers was lower in Caucasians than in Koreans (15.5% vs. 46.2%). CRP levels did not differ between T/T homozygotes (n=946, 1.61+/-2.05 mg/l) and carriers of the C allele (n=173, 1.67+/-1.95 mg/l). Thus, in contrast to Korean males, T-1131>C APOAV variant has no effect on plasma concentrations of CRP in a large group of Caucasian males. Other APOAV variants (Ser19>Trp and Val153>Met) did not also influence plasma concentrations of CRP. APOAV variants are unlikely to be an important genetic determinant of plasma CRP concentrations in Caucasian males.
Keywords: Gene Frequency; Male; polymorfismus genetický; běloši; Adult; C-reaktivní protein; Aged; dospělí; mužské pohlaví; senioři; Polymorphism, Genetic; White People; frekvence genu; lidé; apolipoproteiny A; Humans; apolipoprotein A-V; C-Reactive Protein; Apolipoprotein A-V; Alleles; alely; lidé středního věku; Apolipoproteins A; Middle Aged